ESTUDIOS CITONUCLEOLARES DE LOS TUMORES ENCEFALICOS I CENTROSOMAS Y CENTRIOLOS DE LOS EPENDIMOMAS - GONZALEZ GUZMAN, IGNACIO (Instituto Neuropsiquiatría, CD MEXICO, DF, MEX, 1942)
Allergic reactions, particularly to food, are more common and more severe at the high altitude of Mexico City than at lower levels The feeding programs outlined for infants and young children in the US are not tolerated, particularly with regard to the
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, CITONUCLEOLARES, TUMORES, ENCEFALICOS, CENTROSOMAS, CENTRIOLOS, EPENDIMOMAS; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA